Biology and Clinical Relevance of HCMV-Associated Adaptive NK Cells - Gao, Fei; Zhou, Zhengwei; Lin, Ying; Shu, Guang; Yin, Gang; Zhang, Tianxiang (Frontiers in Immunology, 2022)
Natural killer (NK) cells are an important component of the innate immune system due to their strong ability to kill virally infected or transformed cells without prior exposure to the antigen (Ag). However, the biology of human NK (hNK) cells has largely remained elusive. Recent advances have characterized several novel hNK subsets. Among them, adaptive NK cells demonstrate an intriguing specialized antibody (Ab)-dependent response and several adaptive immune features. Most adaptive NK cells express a higher level of NKG2C but lack an intracellular signaling adaptor, FcεRIγ (hereafter abbreviated as FcRγ). The specific expression pattern of these genes, with other signature genes, is the result of a specific epigenetic modification. The expansion of adaptive NK cells in vivo has been documented in various viral infections, while the frequency of adaptive NK cells among peripheral blood mononuclear cells correlates with improved prognosis of monoclonal Ab treatment against leukemia. This review summarizes the discovery and signature phenotype of adaptive NK cells. We also discuss the reported association between adaptive NK cells and pathological conditions. Finally, we briefly highlight the application of adaptive NK cells in adoptive cell therapy against cancer.